Strategic types, distinctive marketing competencies and organizational performance: A multiple measures‐based study - Conant, Jeffrey S.; Mokwa, Michael P.; Varadarajan, P. Rajan (Strategic Management Journal, 1990)
A new, multi‐item scale for operationalizing Miles and Snow's (1978) strategic typology— defenders, prospectors, analyzers, and reactors—is proposed and field‐tested in this paper. Relatively pure strategic types, identified as those organizations classified similarly using both the newly developed, multi‐item scale and the traditionally employed paragraph approach, are used to analyze the relationship between strategic types, distinctive marketing competencies, and organizational performance. Results of analysis suggest that while the marketing competencies of prospector organizations are superior to those of analyzer, defender, and reactor organizations, all three stable archetypes perform equally well in terms of profitability and outperform reactors. The newly developed strategic types scale performs well and appears to possess significant managerial and research potential. It is theoretically anchored, easily administered, and possesses diagnostic value to both strategists and their organizations.